The Mediating Effect of Organizational Commitment and Occupational Self-Efficacy on Work Engagement - Sandroto, Christine Winstinindah; Alamsyah, Athalia Anabel (International Research Journal of Business Studies, 2024)
The goal of this study is to determine the effect of occupational self-efficacy on work engagement in millennial-generation employees, with organizational commitment as a mediation variable. The population of this research includes members of the millennial generation working in Jabodetabek. The sample comprises 250 respondents; the sampling technique is non-random sampling using the convenience sampling technique. Data processing uses Macro Preacher & Hayes contained in SPSS verse 25, called PROCESS. The study results reveal that occupational self-efficacy has a significant effect on organizational commitment, and organizational commitment has a significant effect on work engagement. Occupational self-efficacy has a significant effect on work engagement, and organizational commitment mediates occupational self-efficacy and work engagement among millennial generation employees who work in Jabodetabek. The direct effect of occupational self-efficacy on work engagement is greater than the indirect effect.